Mechanism of CO2 capture in nanostructured sodium amide encapsulated in porous silica - Tian, Mi (2020)
Nanostructured sodium amide encapsulated in a porous silica gel matrix (“NaNH2-SG”) was investigated for CO2 capture and storage by in-situ gravimetric gas sorption. Exposure of NaNH2-SG to CO2 at 25 °C and 1 bar pressure resulted in ~3.6 wt% CO2 uptake over eight sorption/desorption cycles. Over 90% of the CO2 uptake was non-reversible due to reaction between CO2 and NaNH2 to form sodium carbamate, as confirmed by 13C and 23Na solid-state NMR. Electronic structure calculations suggest a two-stage reaction process involving initial formation and subsequent rearrangement of the carbamate product. This research confirms the feasibility of sequential reactions of nanoparticles in a porous substrate (Na-SG to NaNH2-SG to Na-carbamate-SG), and of CO2 capture by NaNH2-SG nanoparticles stabilised by encapsulation within the porous substrate. This encapsulation method could allow further hygroscopic or reactive starting reagents or compounds to be explored for CO2 capture and long-term storage.